Achievement of prolonged oxygen detection in room-temperature ionic liquids on mechanically polished platinum screen-printed electrodes - Lee, Junqiao; Arrigan, Damien; Silvester, Debbie (American Chemical Society, 2016)
The demonstration of prolonged amperometric detection of oxygen in room-temperature ionic liquids (RTILs) was achieved by the use of mechanical polishing to activate platinum screen-printed electrodes (Pt-SPEs). The RTILs studied were 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([C2mim][NTf2]) and N-butyl-N-methyl-pyrrolidinium bis(trifluoromethylsulfonyl)imide ([C4mpyrr][NTf2]). It was found that voltammetry on polished Pt-SPEs exhibited less deterioration (in terms of voltammogram shapes, stability of peak currents, and appearance of contaminant peaks) from long-term consecutive cycling under 100% vol oxygen flow in both RTILs. The detection capability of these RTIL/Pt-SPE systems, initially subjected to long-term consecutive voltammetric cycling, was also investigated by cyclic voltammetry (CV) and long-term chronoamperometry (LTCA). Current versus concentration plots were linear on both unpolished and polished electrodes for 10-100% vol O2 (using CV) and 0.1-5% vol O2 (using LTCA). However, sensitivities and limits of detection (LODs) from CV were found to improve significantly on polished electrodes compared to unpolished electrodes, particularly in [C2mim][NTf2], but also moderately in [C4mpyrr][NTf2]. The lowest LODs (of ca. 0.1% vol O2) were found on polished SPEs using LTCA, with the most stable responses observed in [C4mpyrr][NTf2]. Calibration graphs could not be obtained on unpolished electrodes in both RTILs using LTCA. The results show that polishing markedly improves the analytical performances of Pt-SPEs for oxygen sensing in RTILs. The reusability of such disposable Pt-SPEs, after the surfaces had been experimentally fouled, was also demonstrated through the use of polishing. Mechanical polishing of Pt-SPE devices offers a viable approach to performance improvement for amperometric gas sensing. © 2016 American Chemical Society.